2019
DOI: 10.1111/1744-9987.12814
|View full text |Cite
|
Sign up to set email alerts
|

Association of OSR‐1 With Vascular Dysfunction and Hypertension in Polycystic Kidney Disease

Abstract: Autosomal‐dominant polycystic kidney disease (ADPKD) is associated with oxidative stress and hypertension development before renal function decline and cardiovascular disease development. Oxidative stress‐responsive kinase‐1 (OSR‐1) participates in the signaling regulating Na+ transport during oxidative stress and also plays a role in the regulation of cell volume and blood pressure. Therefore, we aimed to investigate the potential role of OSR‐1 in ADPKD patients. Eighty ADPKD patients, 80 healthy controls, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Oxidative stress-responsive kinase-1 (OSR-1), which is associated with regulation of Na + transport and cell volume during oxidative stress, has recently been shown to play a role in the regulation of blood pressure in ADPKD [139]. Thus, serum OSR-1 gene expression has been found to be significantly increased in hypertensive ADPKD patients in comparison with normotensive ADPKD counterparts, non-ADPKD hypertensive subjects, as well as healthy individuals [139].…”
Section: Oxidative Stress and Clinical Models Of Ckdmentioning
confidence: 99%
“…Oxidative stress-responsive kinase-1 (OSR-1), which is associated with regulation of Na + transport and cell volume during oxidative stress, has recently been shown to play a role in the regulation of blood pressure in ADPKD [139]. Thus, serum OSR-1 gene expression has been found to be significantly increased in hypertensive ADPKD patients in comparison with normotensive ADPKD counterparts, non-ADPKD hypertensive subjects, as well as healthy individuals [139].…”
Section: Oxidative Stress and Clinical Models Of Ckdmentioning
confidence: 99%
“…OXSR1 contributes to hepatocellular carcinoma cell proliferation and motility by interacting with miR-186-5p as well as LINC01291 (32). Another study showed that OXSR1 expression was associated with vascular dysfunction and hypertension in autosomal-dominant polycystic kidney disease (33). In particular, OXSR1 depletion has a protective effect on the kidney of septic rats and its overexpression relieves miR-93-5p–induced inhibitory effects in LPS-treated HK2 cells (17,34).…”
Section: Discussionmentioning
confidence: 99%